Multi-sensor arm rehabilitation monitoring device - Radzi, Ambar; Hazwaj, Mhd Poad; Abdul Malik, Mohd Ali; Muhammad Shukri, Ahmad; Muhammad Mahadi, Abdul Jamil, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/